An Investigation into Conceptual Metaphors Denoting Life in American and Vietnamese Short Stories - Dinh Thi Mai Anh (Journal of Development Research, 2017)
Metaphor has attracted the attention of scholars interested in language for more than 2000 years (Ning Yu, 1998). Traditionally, metaphor was viewed as a matter of language, only used in literature to embellish discourse (Kovecses, 2010). However, cognitive linguistics presents a different view of metaphor, stating that metaphor is pervasive and essential in language and thought (Lakoff & Johnson, 1980). It is defined as understanding one abstract conceptual domain (target domain), in terms of another concrete one (source domain). The concept of life has been one of the most common target domains, which is hard to fully comprehend without establishing a set of mappings, i.e. a set of systematic correspondences, between this undelineated notion and other better-known ones. Therefore, this study attempts to probe into conceptual metaphors denoting life in nineteen American and nineteen Vietnamese short stories from 1975 to 1991 in the light of Lakoff and Johnsons framework (1980). The two sets of collected data, specifically 89 illustrations in English and 114 in Vietnamese, are compared and contrasted to find out the similarities and differences in the use of these conceptual metaphors between two languages, in the hope to contribute to foreign language teaching, learning, and translating process